Superconductivity in the 2‐Dimensional Homologous Series AMmBi3Q5+m (m=1, 2) (A=Rb, Cs; M=Pb, Sn; Q=Se, Te). Issue 28 (25th April 2018) - Malliakas, Christos D.; Chung, Duck Young; Claus, Helmut; Kanatzidis, Mercouri G.
Abstract: Superconductivity in the two‐dimensional AM m Bi3 Q5+ m family of semimetals is reported. The AMBi3 Te6 ( m =1) and AM2 Bi3 Te7 ( m =2) members of the homologous series with A=Rb, Cs and M=Pb, Sn undergo a bulk superconducting transition ranging from 2.7 to 1.4 K depending on the composition. The estimated superconducting volume fraction is about 90 %. Superconducting phase diagrams as a function of chemical pressure are constructed for the solid solution products of each member of the homologous series, AMBi3− x Sb x Te6− y Se y and AM2 Bi3− x Sb x Te7− y Se y (0≤ x ≤3 or 0≤ y ≤2). The structural flexibility of the ternary AM m M′3 Te5+ m semiconducting homology to form isostructural analogues with a variety of metals, M=Pb, Sn; M′=Bi, Sb, gives access to a large number of electronic configurations and superconductivity due to chemical pressure effects. Abstract : A new family of superconductors is discovered using homologous series. The predictive properties of precisely defined large homologous series for the creation of compounds with trending structural features may reveal a new generation of chalcogenide‐based superconductors.